European SMEs' exposures to ecosystems and natural hazards: A first exploration - Serena Fatica; Ioanna Grammatikopoulou; Dominik Hirschbühl; Alessandra La Notte; Domenico Pisani (European Commission, 2024)
Nature-related financial risks have emerged as critical concerns for policymakers and financial actors. Central to this issue are ecosystem services, which play an integral role in various production processes but may be interrupted due to nature degradation. This article delves into the vulnerability of European SMEs by combining firm-level exposures to ecosystem service dependencies with regional information on the relative abundance of ecosystem services provisioning and the risk of natural hazards. Focusing on long-term debt positions to gauge financial stability implications, the results reveal moderate nature risks for European SMEs at the current stance but also highlight a possible concentration of risks and a need to further refine the use of available indicators.
Keywords: G21; G38; Q5; 330; ecosystem services; natural capital; nature degradation; physical risks; environmental risks; ENCORE; risk management; SMEs